Modulation of Alpha and Beta Oscillations during an n-back Task with Varying Temporal Memory Load - Chen, Youguo; Huang, Xiting (Frontiers in Psychology, 2016)
Temporal information can be retained and manipulated in working memory. Neural oscillatory changes in working memory were examined by varying temporal working memory load. Electroencephalography was obtained from 18 subjects performing a temporal version of the visual n-back working memory task (n = 1 or 2). Electroencephalography revealed that posterior alpha power decreased and temporal region-distributed beta power increased as working memory load increased. This result is consistent with previous findings that posterior alpha band reflects inhibition of task-irrelevant information. Furthermore, findings from this study suggest that temporal region-distributed beta band activity is engaged in the active maintenance of temporal duration in working memory.